2022
DOI: 10.3389/fphys.2022.1020443
|View full text |Cite
|
Sign up to set email alerts
|

Early renal structural changes and potential biomarkers in diabetic nephropathy

Abstract: Diabetic nephropathy is one of the most serious microvascular complications of diabetes mellitus, with increasing prevalence and mortality. Currently, renal function is assessed clinically using albumin excretion rate and glomerular filtration rate. But before the appearance of micro-albumin, the glomerular structure has been severely damaged. Glomerular filtration rate based on serum creatinine is a certain underestimate of renal status. Early diagnosis of diabetic nephropathy has an important role in improvi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 71 publications
(69 reference statements)
0
14
0
Order By: Relevance
“…Recent studies have showed that glomerular injury markers SMAD1 and Podocalyxin were strongly associated with the severity of expansion of the mesangial matrix. And the tubular injury markers Netrin-1, L-FABP, and NGAL were signi cantly higher in diabetic patients than in controls [32] . In addition, lots of microRNAs and lncRNAs were also considered as biomarkers in early diagnosis and treatment of DN [33,34] .…”
Section: Discussionmentioning
confidence: 84%
“…Recent studies have showed that glomerular injury markers SMAD1 and Podocalyxin were strongly associated with the severity of expansion of the mesangial matrix. And the tubular injury markers Netrin-1, L-FABP, and NGAL were signi cantly higher in diabetic patients than in controls [32] . In addition, lots of microRNAs and lncRNAs were also considered as biomarkers in early diagnosis and treatment of DN [33,34] .…”
Section: Discussionmentioning
confidence: 84%
“…This nding is signi cant because uL-FABP increase is a typical expression of tubular damage that is probably one of the rst histologically relevant signs in DN pathophysiology. Subsequently, after the rst damage step, the pathophysiological course of DN most often switches to glomerular involvement and impaired barrier function with albuminuria, overt proteinuria, increased serum creatinine levels, and reduced GFR [45]. Therefore, the fact that this tubular damage marker was demonstrated to be able to predict the onset and progression of glomerular involvement is important and indicates that uL-FABP can detect renal impairment progression in microalbuminuric T2DM patients and that its diagnostic power is also relevant in advanced DN stages as a predictor of disease progression over time [28].…”
Section: Discussionmentioning
confidence: 99%
“…Various pathophysiological mechanisms have been supposed in DN development including hyperglycemia, inflammation, oxidative stress, advanced glycation end products, protein kinase C, and poly(ADP-ribose) polymerase activation [ 11 , 12 , 13 ] ( Figure 1 ). Taken together, these factors are responsible for the morphological impairments occurring at renal site in DN, such as glomerular mesangium hypertrophy, podocytes dysfunction, and extracellular matrix proteins accumulation [ 13 , 14 ]. From a molecular perspective, different cellular and inflammatory signaling pathways such as transforming growth factor- β (TGF- β ), Phosphoinositide 3-kinase-protein kinase B (PI3K-Akt), Mitogen-activated protein kinase (MAPK) family including P38, extracellular signal-regulated kinases (ERK), Nuclear factor kappa-light-chain-enhancer of activated B cells (NF- κ B), and c-Jun N-terminal kinases (JNKs) have been implied in DN pathogenesis [ 13 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Besides classical markers (e.g., urinary cystatin C) [ 10 , 19 , 20 , 21 ], novel promising options are emerging in this research area [ 14 , 20 , 22 ]. In this framework, a pathogenic role for microRNAs (miRNAs) as biomolecules regulating up to 30% of the protein-coding genes in the human genome has been also proposed [ 23 , 24 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%